Can epidemics be noncommunicable? Reflections on the spread of 'noncommunicable' diseases (Medicine Anthropology Theory, 2020)
This article argues that the concept of communicability that is central to the distinction between communicable diseases (CDs) and noncommunicable diseases (NCDs) is poorly conceptualized. The epidemic spread of NCDs such as diabetes, depression, and eating disorders demonstrates that they are communicable, even if they are not infectious. We need to more critically explore how they might be communicable in specific environments. All diseases with epidemic potential, we argue, should be assumed to be communicable in a broader sense, and that the underlying medical distinction between infectious and noninfectious diseases confuses our understanding of NCD epidemics when these categories are treated as synonymous with ‘communicable’ and ‘noncommunicable’ diseases, respectively. The dominant role accorded to the concept of ‘lifestyle’, with its focus on individual responsibility, is part of the problem, rather than the solution, and the labelling of some NCDs as ‘lifestyle diseases’ is misleading. Founded on a critical understanding of global health and globalized medicine, we propose to explore the dynamics of the phenomena of contamination and biosocial contagion in networks. An analytics of biosocial epidemics needs to be developed by a medical anthropology that is engaged in a critical dialogue with both medicine and biology.